Local order in wüstite using a pair distribution function (PDF) approach. (April 2014) - Welberry, T. R.; Goossens, D. J.; Heerdegen, A. P.
Abstract: We show how different aspects of a model of the complex disordered structure of wüstite, Fe1−x O, affect the pair distribution function (PDF) and powder diffraction pattern. The aim is to assess the efficacy of using these techniques to determine details of local structure. The different aspects include the nature of the individual defect clusters, the nature of the paracrystalline superlattice on which they are distributed and the 'size-effect' relaxation of the basic rocksalt FeO matrix around the defects. The results show that PDF data are sensitive to those aspects of the models that have a significant effect on the populations of interatomic spacings but are less able to determine correlation structures in the samples if these do not have a substantial interaction with interatomic separations.